2016
DOI: 10.1103/physreve.94.053311
|View full text |Cite
|
Sign up to set email alerts
|

Grid refinement for entropic lattice Boltzmann models

Abstract: We propose a novel multi-domain grid refinement technique with extensions to entropic incompressible, thermal and compressible lattice Boltzmann models. Its validity and accuracy are accessed by comparison to available direct numerical simulation and experiment for the simulation of isothermal, thermal and viscous supersonic flow. In particular, we investigate the advantages of grid refinement for the set-ups of turbulent channel flow, flow past a sphere, Rayleigh-Bénard convection as well as the supersonic fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 42 publications
3
27
0
Order By: Relevance
“…C p profiles from an experimental study, and a DNS study are also shown for reference. It is to be noted that capturing the C p distribution requires a very high resolution of the sphere [95] while with the current model, we find a reasonable agreement with only 80 points per diameter. The averaged profile of the velocity in the streamwise direction normalized with the freestream velocity at three different locations (x/D 0 = 0.2, 1.6, 3.0) in the wake of the sphere are shown in Fig.…”
Section: Flow Past a Spheresupporting
confidence: 72%
“…C p profiles from an experimental study, and a DNS study are also shown for reference. It is to be noted that capturing the C p distribution requires a very high resolution of the sphere [95] while with the current model, we find a reasonable agreement with only 80 points per diameter. The averaged profile of the velocity in the streamwise direction normalized with the freestream velocity at three different locations (x/D 0 = 0.2, 1.6, 3.0) in the wake of the sphere are shown in Fig.…”
Section: Flow Past a Spheresupporting
confidence: 72%
“…For brevity, we avoid presenting the pure CFD validation as done in [41]. The fluid solver however was thoroughly validated as witnessed by many of our preceding contributions (see, e.g., [42]). Thus, having validated the structural solver, we proceed with benchmarks of the fully coupled FSI scheme.…”
Section: Turek Benchmarkmentioning
confidence: 99%
“…Hence, one may prefer to rely on KBC models to improve the numerical stability of LBMs at a low CPU cost. These collision models are based on an approximation to the minimization problem, and use an analytic formula for the computation of the dynamic relaxation time [12][13][14][15][16][17][18]. They can further decouple the relaxation of shear modes from acoustic and ghost modes, hence, freeing themselves from the generation of spurious vortices induced by the use of a varying shear viscosity in underre-solved conditions.…”
Section: Introductionmentioning
confidence: 99%